CROSS-CULTURAL COMMUNICATION OF FOREIGN TOURISTS WITH LOCAL RESIDENTS - Anindia Safitri; Vethy Octaviani; Fera Indasari (SENGKUNI Journal (Social Science and Humanities Studies), 2020)
The purpose of this study is to find out cross-cultural communication of foreign tourists with local residents. This research uses an interpretive approach with descriptive qualitative methods, with techniques for collecting data through observation, interviews, documentation, and library research. From the results of the research and data analysis, it is known that Cross-Cultural communication has seven elements, including communicators, communicants, messages, media, effects/feedback, atmosphere and disturbances. The communication process between foreign tourists and local residents has not gone well because their communication process is hampered by their own language and also non-verbal errors that both local residents and tourists alike do not understand, that is what inhibits the communication process and causes communication ineffectiveness, therefore it still often causes misunderstandings between the two parties.